Complement Mediated Hemolytic Anemias in the COVID-19 Era: Case Series and Review of the Literature - Fattizzo, Bruno; Pasquale, Raffaella; Bellani, Valentina; Barcellini, Wilma; Kulasekararaj, Austin G. (Frontiers in Immunology, 2021)
The complex pathophysiologic interplay between SARS-CoV-2 infection and complement activation is the subject of active investigation. It is clinically mirrored by the occurrence of exacerbations of complement mediated diseases during COVID-19 infection. These include complement-mediated hemolytic anemias such as paroxysmal nocturnal hemoglobinuria (PNH), autoimmune hemolytic anemia (AIHA), particularly cold agglutinin disease (CAD), and hemolytic uremic syndrome (HUS). All these conditions may benefit from complement inhibitors that are also under study for COVID-19 disease. Hemolytic exacerbations in these conditions may occur upon several triggers including infections and vaccines and may require transfusions, treatment with complement inhibitors and/or immunosuppressors (i.e. steroids and rituximab for AIHA), and result in thrombotic complications. In this manuscript we describe four patients (2 with PNH and 2 with CAD) who experienced hemolytic flares after either COVID-19 infection or SARS-Cov2 vaccine and provide a review of the most recent literature. We report that most episodes occurred within the first 10 days after COVID-19 infection/vaccination and suggest laboratory monitoring (Hb and LDH levels) in that period. Moreover, in our experience and in the literature, hemolytic exacerbations occurring during COVID-19 infection were more severe, required greater therapeutic intervention, and carried more complications including fatalities, as compared to those developing after SARS-CoV-2 vaccine, suggesting the importance of vaccinating this patient population. Patient education remains pivotal to promptly recognize signs/symptoms of hemolytic flares and to refer to medical attention. Treatment choice should be based on the severity of the hemolytic exacerbation as well as of that of COVID-19 infection. Therapies include transfusions, complement inhibitor initiation/additional dose in the case of PNH, steroids/rituximab in patients with CAD and warm type AIHA, plasma exchange, hemodialysis and complement inhibitor in the case of atypical HUS. Finally, anti-thrombotic prophylaxis should be always considered in these settings, provided safe platelet counts.